A Multifactorial Approach for Surveillance of Shigella spp. and Entero-Invasive Escherichia coli Is Important for Detecting (Inter)national Clusters - van den Beld, Maaike J. C.; Reubsaet, Frans A. G.; Pijnacker, Roan; Harpal, Airien; Kuiling, Sjoerd; Heerkens, Evy M.; Hoeve-Bakker, B. J. A. (Dieneke); Noomen, Ramón C. E. A.; Hendriks, Amber C. A.; Borst, Dyogo; van der Heide, Han; Kooistra-Smid, A. M. D. (Mirjam); et al. (Frontiers in Microbiology, 2020)
Shigella spp. and entero-invasive Escherichia coli (EIEC) can cause mild diarrhea to dysentery. In the Netherlands, although shigellosis is a notifiable disease, there is no laboratory surveillance for Shigella spp. and EIEC in place. Consequently, the population structure for circulating Shigella spp. and EIEC isolates is not known. This study describes the phenotypic and serological characteristics, the phenotypic and genetic antimicrobial resistance profiles, the virulence gene profiles, the classic multi-locus sequence types (MLST) and core genome (cg)MLST types, and the epidemiology of 414 Shigella spp. and EIEC isolates collected during a cross-sectional study in the Netherlands in 2016 and 2017. S. sonnei (56%), S. flexneri (25%) and EIEC (15%) were detected predominantly in the Netherlands, of which the EIEC isolates were most diverse according to their phenotypical profile, O-types, MLST types and cgMLST clades. Virulence gene profiling showed that none of the isolates harbored Shiga toxin genes. Most S. flexneri and EIEC isolates possessed nearly all virulence genes examined, while these genes were only detected in approximately half of the S. sonnei isolates, probably due to loss of the large invasion plasmid upon subculturing. Phenotypical resistance correlated well with the resistant genotype, except for the genes involved in resistance to aminoglycosides. A substantial part of the characterized isolates was resistant to antimicrobials advised for treatment, i.e., 73% was phenotypically resistant to co-trimoxazole and 19% to ciprofloxacin. Antimicrobial resistance was particularly observed in isolates from male patients who had sex with men (MSM) or from patients that had traveled to Asia. Furthermore, isolates related to international clusters were also circulating in the Netherlands. Travel-related isolates formed clusters with isolates from patients without travel history, indicating their emergence into the Dutch population. In conclusion, laboratory surveillance using whole genome sequencing as high-resolution typing technique and for genetic characterization of isolates complements the current epidemiological surveillance, as the latter is not sufficient to detect all (inter)national clusters, emphasizing the importance of multifactorial public health approaches.